ChemInform Abstract: A One‐Pot Approach to 4, 5‐Dihydropyrazoles from Ketones, Arylacetylenes, and Hydrazines. Issue 31 (5th August 2014) - Wang, Ying‐Chun; Wang, Heng‐Shan; Huang, Guo‐Bao; Huang, Fu‐Ping; Hu, Kun; Pan, Ying‐Ming
Abstract A general strategy for the three‐component condensation of ketones, hydrazines, and terminal arylalkynes, to give polysubstituted 4, 5‐dihydropyrazoles, generally in good yields, is presented.